Knowledge on Uterine Prolapse among the Married Women in Banepa Municipality, Kavrepalanchowk - Banmali, Shreejana; Kandel, Suresh; Ghimire, Samita; Garu, Krishna; Thapa, Rachana; Upadhyay, Hari Prasad (Journal of College of Medical Sciences-Nepal, 2024)
Background Uterine prolapse is a prevalent issue among women, particularly in low- and middle-income countries like Nepal, significantly impacting their quality of life. Despite its impact, there is a lack of comprehensive knowledge and awareness about this condition among the affected population, leading to delayed interventions and suboptimal healthcare-seeking behaviors. This study aimed to assess the knowledge about uterine prolapse among married women of reproductive age group in Banepa, Kavrepalanchowk. Methods A cross-sectional study was conducted in Banepa Municipality, Nepal, from July to September 2019 after obtaining ethical approval from the Chitwan Medical College Institutional Review Committee. Face-to-face interviews with a total of 251 married women of the reproductive age group were done using a semi-structured questionnaire. Descriptive statistics, Chi-square tests, and multivariate logistic regression models were performed. Results The study revealed that among all the respondents 86.3% had heard about uterine prolapse, with 42.5% demonstrating satisfactory knowledge. Religious affiliation, education, average monthly income of the family and prime source of knowledge on uterine prolapse were found to be significantly associated in bivariate logistic regression while taking them to the multivariate analysis education status (AOR=6.342, p=0.010) and religious affiliation (AOR=6.138, p=0.003) were found significantly influencing the knowledge level. Conclusions The study revealed significant knowledge gaps on uterine prolapse among married women in Banepa Municipality, Nepal, highlighting the imperative for targeted educational interventions. Socioeconomic factors and healthcare access influence awareness, emphasizing the need for culturally sensitive initiatives.